Emerging Roles of the Intraflagellar Transport System in the Orchestration of Cellular Degradation Pathways - Finetti, Francesca; Capitani, Nagaja; Baldari, Cosima T. (Frontiers in Cell and Developmental Biology, 2019)
Ciliated cells exploit a specific transport system, namely the intraflagellar transport (IFT) system, to ensure the traffic of molecules from the cell body to the cilium. However, it is now clear that IFT activity is not restricted to cilia-related functions. This is strikingly exemplified by the observation that IFT proteins play important roles in cells lacking a primary cilium, such as lymphocytes. Indeed, in T cells the IFT system regulates the polarized transport of endosome-associated T cell antigen receptors and signaling mediators during assembly of the immune synapse, a specialized interface that forms on encounter with a cognate antigen presenting cell and on which T cell activation and effector function crucially depend. Cellular degradation pathways have recently emerged as new extraciliary functions of the IFT system. IFT proteins have been demonstrated to regulate autophagy in ciliated cells through their ability to recruit the autophagy machinery to the base of the cilium. We have now implicated the IFT component IFT20 in another central degradation process that also controls the latest steps in autophagy, namely lysosome function, by regulating the cation-independent mannose-6-phosphate receptor (CI-MPR)-dependent lysosomal targeting of acid hydrolases. This involves the ability of IFT20 to act as adaptor coupling the CI-MPR to dynein for retrograde transport to the trans-Golgi network. In this short review we will discuss the emerging roles of IFT proteins in cellular degradation pathways.